Initial Steps In Writing and Submitting A Research Paper - Denise Pinheiro Falcão; Anthony Terrence O'Brien; Rivadávio Fernandes Batista de Amorim; Heitor Moreno; Felipe Fregni; Maria Regina Chalita (Brazilian Society of Geriatrics and Gerontology, 2024)
BACKGROUND: This article is part of a special series designed to help authors in the process of scientific writing. OBJECTIVE: To address the steps that should precede the writing and submission of a research paper in order to optimize the process. METHOD: The authors discussed among them some strategies that should be adopted before properly starting the manuscript writing. RESULTS: Key strategies were organized into five thematic groups, namely: 1) How to prepare yourself for writing, 2) How to organize and prepare the writing tools, 3) How to elaborate a draft, 4) How to choose a journal, and 5) Who should be an author. CONCLUSION: Key strategies should be adopted before writing and submitting a research paper. Such strategies might improve the author's performance, optimize the time spent, and promote a high-quality communication writing, more pleasantly.